SEX EDUCATION MELALUI BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA - ANIK SUPRIYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The existence of the COVID-19 pandemic, which requires the education process to be carried out online, ultimately creates its own problems, both in terms of educators, the learning process itself and also problems from students. In this case students become less controlled because there is no direct supervision from the teacher, while parents have many limitations in their supervision, in the area where the researcher teaches most of the parents migrate to the city so that students only live with their grandmothers/grandparents or other families. so that it is not too focused on supervising students, besides that with the existence of advanced technology (gadgets) it increasingly opens up opportunities for students to socialize and communicate in cyberspace. Currently, sexual activities are also growing, people can easily open pornographic sites, and can have sex virtually, and so on. It is these possibilities that prompted the author to carry out this research. Through group guidance services with sociodrama techniques, it is expected to be able to provide understanding to students about the dangers of free sex even though it is done virtually. This article is a Best Practice that has been carried out by researchers. The activity was carried out in 2 meetings, in the first meeting, group guidance was carried out with the material